Pengenalan Saham Sebagai Alternatif Investasi Bagi Masyarakat Desa Negeri Sakti Kabupaten Pesawaran - Sobita, Nindya Eka; Harori, M Iqbal; Palupi, Rendy Satya Aji; Aini, Iqrima (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Today's community economic needs are getting bigger, costs in the food, education and transportation sectors are becoming increasingly uncertain, not to mention the eternal enemy of the financial sector, namely inflation, which is a scourge in itself for people's finances, so that even if you keep money under the bed or in the bank, inflation will continues to haunt and eat up the value of our money, like how many decades ago, with one hundred thousand dollars worth of money, a woman at the market could buy many variations of vegetables with a large stock and enough for one week, but now with the value of that money she can only buy 1 type of food and enough for 1 meal in the family. So this community service aims to share knowledge with the public that investing in stock market can be an option for the community to reduce inflation and also become an asset in the future.